Dehydrogenation of ethanol to acetaldehyde upon copper supported on carbon catalysts - Е. А. Ponomareva; Е. V. Egorova; D. А. Bokarev; A. S. Parastaev (Тонкие химические технологии)
The process of ethanol dehydrogenation to acetaldehyde upon different copper supported on carbon catalysts has been studied. Different carbon materials – activated carbon Norit, carbon-carbon composite sibunit and activated carbon fibers (ACF) – were used as a support for the catalyst. The BET surface area as well as the porous structure of the materials were determined with the use of N2 adsorption-desorption technique. The catalysts prepared by wetness impregnation contained 5% of Cu. The effect of the carrier texture on the distribution of active metal has been shown using scanning electron microscopy. Copper deposited on ACF was well distributed in comparison with the other supports studied and had an average particle size of 20 nm. This led to higher activity of the 5% Cu/ACF catalyst. Besides, it appeared more selective in the process of dehydrogenation.